Analisis Proses dan Implikasi Perubahan Kebijakan Umum Anggaran Serta Prioritas dan Plafon Anggaran Sementara Terhadap Penyusunan Perubahan APBD Tahun Anggaran 2025 (Studi Kasus Pada Badan Pengelola Keuangan Dan Aset Daerah) - Lambertus, Yohanes; Herdi , Henrikus; Yecci Noeng , Amanda (Jurnal Projemen UNIPA, 2026)
This study aims to analyze the process and implications of changes in the General Budget Policy (KUA) and the Temporary Budget Priorities and Ceilings (PPAS) on the preparation of the Revised Regional Revenue and Expenditure Budget (APBD) for the Fiscal Year 2025 at the Regional Financial and Asset Management Agency (BPKAD) of Sikka Regency. The research employs a qualitative descriptive approach using secondary data in the form of planning and budgeting documents as well as internship activity results. The findings indicate that the preparation process of KUA–PPAS has been conducted in accordance with applicable regulations, starting from planning based on RPJMD and RKPD, formulation by the Regional Government Budget Team (TAPD), and discussions with the Regional House of Representatives (DPRD), supported by the SIPD system. Changes in KUA–PPAS are influenced by internal factors such as discrepancies in revenue and expenditure realization, program shifts, and the utilization of budget surplus (SiLPA), as well as external factors including central government policy changes, macroeconomic conditions, and emergency situations.